Dismantling Epistemic Injustice in Early Childhood Education: Bringing Forward Counternarratives of Marginalized Children and Families to Disrupt Developmentalism - Menon, Nidhi (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
Early childhood education and care is heavily influenced by epistemologies rooted in the perspectives of white European men, which prioritize neoliberal ideals of developmental knowledge, standardization, and assessment. These frameworks limit the scope of research, policy, and pedagogy in the field. This paper examines how developmentalism, as a manifestation of white patriarchal knowledge, functions as an epistemic injustice that marginalizes young refugee children and families in their schooling experiences during resettlement in Ontario, Canada. Through the lenses of Black feminist thought and the sociology of childhood, this analysis highlights how developmentalist discourses contribute to deficit-based perspectives of refugee children, shaping their educational experiences and reinforcing their marginalization.